Evaluating the Decoding the Disciplines paradigm that is used for developing disciplinary habits of mind: A systematic literature review - Mohamed, S.; Bayat, A. (South African Journal of Higher Education, 2022)
This article reports on a systematic review of the literature to evaluate the Decoding the Disciplines paradigm (henceforth “DtD”) in the development of expert disciplinary habits of mind in student learning. A search was conducted utilising various databases (EBSCOhost, DOAJ, JSTOR, SAGE Journals Online, Scopus, Wiley Online and uKwazi) (Library Search Engine) for the period 2004 to 2020. More than 500 papers, retrieved from nine scholarly databases, were screened, based on title and abstract, resulting in 33 shortlisted papers for analysis. The researcher and one independent reviewer assessed the methodological quality of the shortlisted articles. Five countries are represented in this study. The results of this review highlighted the impact that the DtD has on the development of expert ways of thinking in learners. The case studies attest to the fact that several insights, namely 1) Concretising abstract phenomena; 2) Overcoming emotional bottlenecks; 3) Making expert habits of mind explicit to the learner; 4) Trans-disciplinary approaches and the T-Shaped learner and 5) Synergies between threshold concepts and information literacy habits of mind, are capabilities that the DtD process could cultivate in student learning to overcome complex bottlenecks.